The evolutionary biology of plants - Niklas, Karl Josef (Univ. of Chicago Press, 1997)
"After presenting key evolutionary principles, Niklas recounts the saga of plant life from its origins to the radiation of the flowering plants. To investigate how living plants might have evolved, Niklas conducts a series of computer-generated "walks" on fitness "landscapes," arriving at hypothetical forms of plant life strikingly similar to those of today and the distant past. He concludes with an extended consideration of molecular biology and paleontology." (Publisher's Web page).